Immune modulation as a treatment strategy in angioimmunoblastic T-cell lymphoma (Hematology Meeting Reports, 2009)
Angioimmunoblastic T-cell lymphoma (AITL) is a rare and complex lymphoproliferative disorder. The lack of standard and effective treatments to date poses significant challenges for physicians treating patients with AITL. There is little consensus on the optimal chemotherapy regimen in either the frontline treatment or relapsed setting. In several series the median survival of AITL patients has been estimated to be between 11 and 30 months, with only 30% of patients surviving more than 2 years.